2009
DOI: 10.1111/j.1439-0434.2008.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Burdock Fructooligosaccharide Induces Changes in the Production of Salicylates, Activates Defence Enzymes and Induces Systemic Acquired Resistance to Colletotrichum orbiculare in Cucumber Seedlings

Abstract: The ability of burdock fructooligosaccharide (BFO), a type of linear fructooligosaccharide extracted and isolated from the roots of Arctium lappa, to induce systemic acquired resistance (SAR) was studied in cucumber seedlings. BFO strongly induced changes in salicylic acid (SA) and SA-glucoside (SAG) in BFO-treated leaves, and similar changes of SA and SAG were also found in untreated leaves of the same seedling. The level of SA in the first leaves sprayed with BFO (5.0 g ⁄ l) increased by 3.6 times after 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In keeping with the findings of Billett et al (Monties et al, 1976) and the observed fragmentation pattern this compound has been suggested as p-coumaric acid-O-glycoside. p-coumaric acid and its isomer were proposed for peaks 38 and 45, which has been reported previously (Gómez-Romero et al, 2011;Bellés et al, 2008;Maksimovic et al, 2007;Daayf, Bel-Rhild, & Belanger, 1997;Daayf, Schmitt, & Bélanger, 1997;Krauze-Baranowsk & Cisowski, 2001;Laporta et al, 2007;Al-Duais et al, 2009;Monties et al, 1976;Zhang et al, 2009;Wang et al, 2008).…”
Section: Simple Phenolic Acid Derivativesmentioning
confidence: 77%
See 1 more Smart Citation
“…In keeping with the findings of Billett et al (Monties et al, 1976) and the observed fragmentation pattern this compound has been suggested as p-coumaric acid-O-glycoside. p-coumaric acid and its isomer were proposed for peaks 38 and 45, which has been reported previously (Gómez-Romero et al, 2011;Bellés et al, 2008;Maksimovic et al, 2007;Daayf, Bel-Rhild, & Belanger, 1997;Daayf, Schmitt, & Bélanger, 1997;Krauze-Baranowsk & Cisowski, 2001;Laporta et al, 2007;Al-Duais et al, 2009;Monties et al, 1976;Zhang et al, 2009;Wang et al, 2008).…”
Section: Simple Phenolic Acid Derivativesmentioning
confidence: 77%
“…The fragment ion at m/z 137.0236 was already reported elsewhere (Zhang, Wang, Liu, & Chen, 2009;Fofana et al, 2002;Segarra, Jáuregui, Casanova, & Trillas, 2006).…”
Section: Simple Phenolic Acid Derivativesmentioning
confidence: 91%
“…Recently, it was found that short inulin-type fructans (fructooligosaccharides, FOS) from Arctium lappa or burdock (burdock fructooligosaccharides, BFO) prime plant defenses in different pathosystems. (Wang et al, 2009; Zhang et al, 2009; Sun et al, 2013). Priming, a process believed to occur at the expense of minimal amounts of ATP, brings plants in a “ready-to-go” status, preparing them for a faster and stronger response to future (a)biotic stresses (Conrath, 2015).…”
Section: Sugars As Damps: the Case Of Plant Fructansmentioning
confidence: 99%
“…However, the use of fructans such as inulin may be able to improve and delay diseases in plants as they that can act as a molecular pattern associated with damage and active defense mechanisms that prevent attack by pathogens . For example, fructans isolated from Arctium lappa , activated pathogen‐response proteins, like β‐1,3 glucanases and peroxidases in cucumber plants . Therefore, the use of inulin as an elicitor for disease control is an alternative to keep plants protected due to the delay in infection by pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Fructans are a class of elicitors that show a beneficial effect on the control of diseases, for example in cucumber plants, because they induce resistance mechanisms and control postharvest diseases; they also present antimicrobial activities against pathogens . The inulin from Dahlia (I) is a fructan that can act as a molecular pattern associated with damage and activate the innate immune response of the plant through receptors .…”
Section: Introductionmentioning
confidence: 99%